Are premonitory urges a prerequisite of tic inhibition in Gilles de la Tourette syndrome?. Issue 10 (28th July 2012) - Ganos, Christos; Kahl, Ursula; Schunke, Odette; Kühn, Simone; Haggard, Patrick; Gerloff, Christian; Roessner, Veit; Thomalla, Götz; Münchau, Alexander
Abstract : Background: Despite the common notion that premonitory urges facilitate tic inhibition, no studies have investigated this question systematically. We examined the relation of the trait of premonitory urges with tics and tic suppression. We hypothesised that patients with more urges would be more efficient at inhibiting tics. Methods: 15 adult (14 men, mean age 32.2±7.9 years) pure Gilles de la Tourette syndrome patients participated. Tic severity was evaluated using the modified Rush Video Scale and by employing the Yale Global Tic Severity Scale. Tic suppressibility was assessed from videos of additional periods where patients were instructed to maximally suppress their tics. Rush score based inhibition potency was synthesised by combining the scores in the two conditions. A measure of pure motor tic inhibition potency was also generated based on the number of motor tics alone. Premonitory urges were assessed by the Premonitory Urge for Tics Scale. Results: All participants reported urges preceding their tics and were able to voluntarily suppress their tics. However, there was no correlation between urge scores and the Rush score based inhibition potency or the pure motor tic inhibition potency. Scores of the Premonitory Urge for Tics Scale correlated with the interference subscale item of the Yale Global Tic Severity Scale. Conclusions: Urges and tic inhibition are not directly related. There seem to exist at least two distinct neurophysiological systems of urge/tic generation and tic control in adult Gilles de la Tourette syndrome patients.